Peran Perempuan Dalam Meningkatkan Pendapatan Keluarga Pada Industri Olahan Pala Di Desa Hilir, Kabupaten Aceh Selatan - Zulkarnain Zulkarnain; Irwan A Kadir; Bagio Bagio; Sri Novi Afriyaji (Universitas Teuku Umar, 2021)
South Aceh Regency is very well known as a nutmeg-producing area. The people of South Aceh process nutmeg so that it has a high economic value so that it can be additional income for them. In general, actors in home-based economic activities are housewives. It is suspected that there are several factors such as age, education, marital status, number of family members, husband's income, and number of working family members which influence housewives to work in the nutmeg processed home industry. The purpose of this study was to determine the role of women who work in the nutmeg-processed home industry in increasing family income in Hilir Village, Tapaktuan District, where the research method used was a survey method using a questionnaire, while the analytical tool used was logistic regression analysis. Based on the research results, three variables significantly influence the tendency of women to work in the nutmeg-processed home industry in Hilir Village, Tapaktuan District, namely the education variable, the number of dependents, and the number of working family members. The contribution of the income of women who work in the nutmeg processed home industry is 35%, which shows that the income received by women is very supportive of the family economy.